Annual Plan 2006-07 Background Note 2006-07 - Planning Commission (Planning Commission, 2006)
In the official level meeting held between FR division and other officers resources estimated for Annual Plan 2006-07 of Andhra Pradesh worked out to Rs.20512.36 crores. However, outlay proposed for Annual Plan 2006-07 as indicated in the draft Annual Plan document submitted by the Govt. is for 2006-07 is of the order Rs 19551.91 crores. A statement showing proposed sectoral / scheme-wise break up of outlays is given in Annexure-II.
Planning Commission, State Plan Division
Planning Commission State Plan Division